(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the perception of nursing students in relation to palliative care, as well as to identify the difficulties and insecurities related to patients undergoing palliative care. Methodology: This is prospective qualitative-quantitative research carried out in a private institution in southern Brazil. For data collection, a sociodemographic questionnaire and a semi-structured questionnaire were applied to a target population of 30 nursing students. Data production took place through a semi-structured interview from July to August 2022. Data were processed by the IRaMuTeQ software, and lexical analysis was performed. Results: It was observed that most participants are female and have an average age of 21 to 39 years, it was identified that most participants do not feel prepared to deal with palliative patients, they also mentioned insecurity and fear. Conclusion: With the present study it was possible to conclude that academics are not prepared to take care of palliative patients as well as to face the process of death and dying of the patient.